Evolutionary Dynamics of the Cellulose Synthase Gene Superfamily in Grasses. Issue 3 (21st May 2015) - Schwerdt, Julian G.; MacKenzie, Katrin; Wright, Frank; Oehme, Daniel; Wagner, John M.; Harvey, Andrew J.; Shirley, Neil J.; Burton, Rachel A.; Schreiber, Miriam; Halpin, Claire; Zimmer, Jochen; Marshall, David F.; et al.
Abstract : Variable selection pressure in the cellulose synthase gene superfamily reveals positions of amino acids under selection and unexpected evolutionary histories for key genes. Abstract: Phylogenetic analyses of cellulose synthase ( CesA ) and cellulose synthase-like ( Csl ) families from the cellulose synthase gene superfamily were used to reconstruct their evolutionary origins and selection histories. Counterintuitively, genes encoding primary cell wall CesAs have undergone extensive expansion and diversification following an ancestral duplication from a secondary cell wall-associated CesA . Selection pressure across entire CesA and Csl clades appears to be low, but this conceals considerable variation within individual clades. Genes in the CslF clade are of particular interest because some mediate the synthesis of (1, 3;1, 4)-β-glucan, a polysaccharide characteristic of the evolutionarily successful grasses that is not widely distributed elsewhere in the plant kingdom. The phylogeny suggests that duplication of either CslF6 and/or CslF7 produced the ancestor of a highly conserved cluster of CslF genes that remain located in syntenic regions of all the grass genomes examined. A CslF6 -specific insert encoding approximately 55 amino acid residues has subsequently been incorporated into the gene, or possibly lost from other CslFs, and the CslF7 clade has undergone a significant long-term shift in selection pressure. Homology modeling and molecular dynamics of the CslF6 protein were used to define the three-dimensional dispositions of individual amino acids that are subject to strong ongoing selection, together with the position of the conserved 55-amino acid insert that is known to influence the amounts and fine structures of (1, 3;1, 4)-β-glucans synthesized. These wall polysaccharides are attracting renewed interest because of their central roles as sources of dietary fiber in human health and for the generation of renewable liquid biofuels.